Kepatuhan terhadap Protokol Kesehatan Covid-19 di Ruang Publik - Dwiyanti Hanandini; Wahyu Pramono (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
Population non-compliance in carrying out strict health protocols in public spaces has the potential to be infected with covid 19, therefore the government limits population crowds in public spaces. This article aims to explain the level of community compliance with health protocols in public spaces. The survey was conducted on 100 residents using questionnaires and observations in public places. Data were analyzed using the statistical packed for social sciences (SPSS) program. The research was conducted in the city of Padang. The research findings show that the level of compliance of the population in complying with the covid-19 health protocol is generally quite high, although there are several health protocols that are not adhered to in certain public areas. In particular, residents are very obedient in implementing the covid-19 health protocol when at malls and recreational areas. While places of worship are places where many residents violate the covid-19 health protocol.